Analisis Perbandingan Metode Proyeksi Penduduk untuk Estimasi Kebutuhan Air Baku 2020–2045 - Habrio Ilva; Aria Bagiasa Chidmahdjati (LPPM Universitas Abdurrab, 2026)
Continuous population growth directly affects raw water demand as a fundamental component in planning sustainable water supply systems. This study aims to comparatively analyze the geometric, arithmetic, and linear regression (least square) methods in projecting population growth for the period 2020–2045 and to estimate raw water demand based on these projections. A quantitative approach was employed using secondary population data from 2010–2024. Statistical analyses included the calculation of mean, standard deviation, and correlation coefficients to evaluate the consistency and reliability of each method. The results indicate that all methods demonstrate a strong positive correlation with time, with the highest correlation coefficient observed in the arithmetic method (0.9967), followed by the geometric method (0.9957), and linear regression (0.9444). Population projections for 2045 reveal variation among the methods, with the linear regression model producing the highest estimate. Consequently, projected raw water demand increases steadily toward the end of the projection period. This study provides a comparative statistical framework that can support more accurate and sustainable raw water supply planning in the future